English Language Development in the Nigerian Society: A Derivative of Advertising Communications - Dalamu, Taofeek Olaiwola (Complutense Journal of English Studies, 2018)
Language, a central device in social domains, began from somewhere; and it has witnessed unstoppable development. The growing behaviour influenced this study with a goal to appraise the contributions of advertising in Nigeria to the development of English. Thus, thirty-two creative-cum-new lexicons of MTN® and Etisalat® served as analytical data. Morphological tools of derivation, compounding and blending assisted in processing the formation of novel words. The study revealed that the competitive market had informed copywriters to chart a new credible course. That spirit has motivated advertising experts to create exciting lexicons, which are convenient to sensitise readers. Given that factor, word formation processes become arbitrary where phonemic units [k], [z], [j] and [a] were employed to realise morphemic elements of Kulturefest, callertunez and Nigeria. Some formations follow compounding procedures (F@stLink, biztime; 9javaganza and easyflex) as well as deviations (Thank Yous, hynet; wwwhenever and freeeee) to achieve persuasion. The construction of lexicons is fundamental, where MTN adopts Y’ello and Etisalat associates with 0809ja as business identities. As these constructs are fascinating and functional in the social system, the study suggested that lexicographers might take advantage of the development to integrate new lexemes in dictionaries, as observed from the Nigerian perspectives.